2013
DOI: 10.1093/bjsw/bcs196
|View full text |Cite
|
Sign up to set email alerts
|

Places of Sanctuary for 'the Undeserving'? Homeless People's Day Centres and the Problem of Conditionality

Abstract: This paper is an exploration of a dilemma that is central to the place of day centres in tackling single homelessness, and raises issues for social work more generally. On the one hand, day centres provide vital services to a vulnerable group in a safe, nonthreatening and non-judgemental setting; on the other hand, in doing so, they are believed to impede opportunities for personal change. The paper draws on findings from a research study which compared and contrasted the priorities of single homeless people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 13 publications
1
35
0
1
Order By: Relevance
“…These (predominantly but not exclusively faith-based) services tend to adopt an 'unconditional' open-door approach, which aims to welcome all regardless of their personal circumstances and hold no expectation, even if they may still 'hope' , that service users will engage with support services and/or alter their lifestyle (Cloke et al, 2005;Johnsen, 2014). Most aim to foster a therapeutic environment or 'sanctuary' (Bowpitt et al, 2013) which avoids 'pressuring' homeless people to alter their behaviour, but rather focuses on supporting them to change if and when they self-identify as being ready to do so.…”
Section: Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…These (predominantly but not exclusively faith-based) services tend to adopt an 'unconditional' open-door approach, which aims to welcome all regardless of their personal circumstances and hold no expectation, even if they may still 'hope' , that service users will engage with support services and/or alter their lifestyle (Cloke et al, 2005;Johnsen, 2014). Most aim to foster a therapeutic environment or 'sanctuary' (Bowpitt et al, 2013) which avoids 'pressuring' homeless people to alter their behaviour, but rather focuses on supporting them to change if and when they self-identify as being ready to do so.…”
Section: Tolerancementioning
confidence: 99%
“…Likewise, a number of scholars have drawn normative distinctions between the ostensibly 'caring' approach of 'low threshold' services on the one hand, and the apparently 'callous' approach of services that deploy more 'conditional' techniques (see for example Bowpitt et al, 2013;Cloke et al, 2010;Evans, 2011;Fopp, 2002;Scanlon & Adlam, 2008). Studies illuminating compassionate or ambivalent motives underpinning both types of initiatives go some way to problematizing these accounts (see for example Deverteuil et al, 2009;Forrest, 2014;Hansen Lofstrand, 2015;Johnsen & Fitzpatrick, 2010;Laurenson & Collins, 2007;Murphy, 2009;Scullion et al, 2015), but negative portrayals of the use of social control in this field nevertheless predominate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is not safe to assume that because the motives of those involved -to offer support, hospitality and sanctuary to people in needare manifestly legitimate (Bowpitt et al, 2014;Cloke et al, 2005Cloke et al, , 2010, the outcomes are necessarily ethical (Fitzpatrick and Johnsen, 2009). One key benefit of incorporating a consequentialist dimension within our framework is to allow for ethical judgements about the costs of inaction, or non-intervention, alongside those of intervention 4 .…”
Section: Effectiveness Proportionality and Balancementioning
confidence: 99%
“…Cross-European research (FEANTSA, 2010) has shown that the requirements to enter services are increasingly dependent on specific eligibility criteria. The conditionality of social services and organisations that closely guard their territory is widespread (Quilgars, Fitzpatrick, & Pleace, 2011); even in nonjudgemental and nonthreatening settings that are directly accessible, such as day centres, similar developments can be discerned, as for example, in the UK (e.g., Bowpitt, Dwyer, Sundin, & Weinstein, 2013). In search of solutions for this conditionality, several Anglo-Saxon and European countries have proposed new approaches to housing, such as the USA "continuum of care", the "staircase of transition" and the "housing first" approaches (Busch-Geertsema, 2010;Hoch, 2000).…”
Section: Concluding Reflectionsmentioning
confidence: 99%